1994
DOI: 10.1128/iai.62.7.2874-2884.1994
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes in host defense against bacterial translocation from the gastrointestinal tract

Abstract: Flow cytofluorometric analyses of lymphocytes harvested from the mesenteric lymph node (MLN), mucosal epithelium, and lamina propria of C57BL/6 mice demonstrate that expression of a/Il or y/6 T-cell receptors (TCR) and CD4 or CD8 molecules by T lymphocytes in the intestinal immune system varies depending upon their anatomic location. The MLN contained equivalent numbers of CD4+ and CD8+ T cells, the vast majority of which were a/I TCR positive (a/Il TCR+). The lamina propria T cells were predominantly CD4+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 63 publications
2
47
0
2
Order By: Relevance
“…The process by which bacteria and their products migrate from the GIT to the bloodstream and other organs is called "bacterial translocation," which was first described as a clinical phenomenon by Wolochow and colleagues in the 1960s (1) and was investigated experimentally by Berg and coworkers in the 1980s (2)(3)(4)(5)(6)(7)(8)(9)(10). The latter set of studies defined several risk factors that contribute to translocation, including disruption of gut microflora by antibiotics (4,6), damage or increased permeability of the intestinal epithelial barrier (4,9,11,12), and the health status of the host (4,5,7,8,(10)(11)(12)). In addition, several studies have established an association between the intestinal microflora and systemic infections in immunocompromised individuals (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…The process by which bacteria and their products migrate from the GIT to the bloodstream and other organs is called "bacterial translocation," which was first described as a clinical phenomenon by Wolochow and colleagues in the 1960s (1) and was investigated experimentally by Berg and coworkers in the 1980s (2)(3)(4)(5)(6)(7)(8)(9)(10). The latter set of studies defined several risk factors that contribute to translocation, including disruption of gut microflora by antibiotics (4,6), damage or increased permeability of the intestinal epithelial barrier (4,9,11,12), and the health status of the host (4,5,7,8,(10)(11)(12)). In addition, several studies have established an association between the intestinal microflora and systemic infections in immunocompromised individuals (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Translocation of enteric bacteria depends on disturbance of the intestinal microecology with subsequent bacterial overgrowth (7,10,11,36), impaired host immunity (4,6,20), or physical disruption of the gut mucosal barrier (29,32). Accumulating evidence from human and animal studies suggests that factors such as trauma (18,34) endotoxemia (13,15), hemorrhage (1,2,26), and thermal injury (12,14,30) promote bacterial translocation.…”
mentioning
confidence: 99%
“…Moreover, T-cell depletion not only caused accumulation of bacteria in MLN in healthy rats but also increased bacterial numbers observed in MLN of alcohol-and burn-injured rats and did cause spreading of bacteria to extraintestinal sites (55). Therefore, it appears that appropriate activation of intestinal T cells is critical in maintaining immunity against the translocation of enteric bacteria (108). Additional studies showed the ability of adoptively transferred T cells to confer protection against a number of bacterial infections including E. coli (109).…”
Section: Mechanisms and Immunological Aspectsmentioning
confidence: 99%